The Chinese-Indonesian Meaning Shift in Chinese Drama Series 你是我的荣耀 [Nǐ Shì Wǒ de Róngyào] - Wahyu Dwi Hidayatullah; Octi Rjeky Mardasari; Deddy Kurniawan; Qin Tongxin (Universitas Negeri Malang, 2024)
This research discusses the meaning shift in Chinese to Indonesian translation of Chinese drama series 你是我的荣耀 [Nǐ Shì Wǒ de Róngyào]. Using Simatupang's theory, this study aims to identify and analyze the types of meaning shifts that occur. Data were collected from the first two episodes of the drama series and analyzed through descriptive qualitative method. The results show that there are three types of meaning shift, namely meaning shift due to cultural influence, meaning shift from specific to generic, and meaning shift from generic to specific. The shift in meaning due to cultural influence is the most frequent, influenced by the use of 成语 [chéngyǔ], particles, figurative words, catchwords, and differences in cultural context between BSu and BSa. The shift from specific to generic occurs when the translator simplifies specific terms to make them easier for the audience to understand. The shift of meaning from generic to specific occurs when the translator adds additional context to make it easier for the audience to understand. This study shows the importance of cultural understanding in the translation process to ensure an accurate translation that can be understood by the target language audience. Future researchers are advised to expand the research by analyzing more episodes or series from various genres for a deeper understanding of meaning shifts, and students studying translation are advised to learn more about the impact of meaning shifts on audience comprehension of translated texts.